2017
DOI: 10.2141/jpsa.0160099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylanase Supplementation and Citric Acid on Performance, Ileal Nutrients Digestibility, and Gene Expression of Intestinal Nutrient Transporters in Broilers Challenged with <i>Clostridium perfringens</i>

Abstract: This study was conducted to evaluate the effects of xylanase and citric acid (CA) on growth, digesta pH, ileal populations of Clostridium perfringens and lactic acid bacteria, ileal nutrient digestibility, digestive enzyme activity, and mRNA expression of intestinal nutrient transporters in starter broilers challenged with C. perfringens. The experiment was conducted in a 2×2 factorial arrangement with two levels of CA (0 and 30 g/kg) and 2 levels of xylanase (0 and 200 mg/kg). Each of the four dietary treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
9
2
Order By: Relevance
“…These improvements are confirmed by the previous results of Guo et al, who demonstrated that the addition of Xyl upregulated the expression of the sodium–glucose cotransporter 1 and IGFR genes in broiler chickens [40]. Furthermore, Hosseini et al reported that the inclusion of Xyl improved the expression of GHR and IGFR genes [41]. Moreover, ACC and FAS encode a biotin-dependent enzyme which is involved in the biosynthesis of fatty acids via the catalyzation of the irreversible carboxylation of acetyl-CoA for malonyl-CoA production [42].…”
Section: Resultssupporting
confidence: 77%
“…These improvements are confirmed by the previous results of Guo et al, who demonstrated that the addition of Xyl upregulated the expression of the sodium–glucose cotransporter 1 and IGFR genes in broiler chickens [40]. Furthermore, Hosseini et al reported that the inclusion of Xyl improved the expression of GHR and IGFR genes [41]. Moreover, ACC and FAS encode a biotin-dependent enzyme which is involved in the biosynthesis of fatty acids via the catalyzation of the irreversible carboxylation of acetyl-CoA for malonyl-CoA production [42].…”
Section: Resultssupporting
confidence: 77%
“…These results agree with [ 53 ], who showed an upregulated sodium–glucose cotransporter 1 and IGFR genes in broilers fed dietary NSP enzymes. Furthermore, [ 54 ] reported that the inclusion of the NSP enzyme improved the expression of GHR and IGFR genes. In addition, CSM content high polyphenols which have good roles in enhancing the gene expressions related to growth [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed by Guo et al [ 37 ] who reported that the inclusion of xylanase in the broiler chicken diet up-regulated the expression of the jejunal sodium-glucose cotransporter 1 ( SGLT1 ) and PEPT1 genes in broiler chickens. Similarly, xylanase supplementation up-regulated the expression of jejunal SGLT1 and PEPT1 genes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%